Occupational radiation and haematopoietic malignancy mortality in the retrospective cohort study of US radiologic technologists, 1983–2012. (23rd September 2020) - Linet, Martha S; Little, Mark P; Kitahara, Cari M; Cahoon, Elizabeth K; Doody, Michele M; Simon, Steven L; Alexander, Bruce H; Preston, Dale L
Abstract : Objectives: To evaluate cumulative occupational radiation dose response and haematopoietic malignancy mortality risks in the US radiologic technologist cohort. Methods: Among 110 297 radiologic technologists (83 655 women, 26 642 men) who completed a baseline questionnaire sometime during 1983–1998, a retrospective cohort study was undertaken to assess cumulative, low-to-moderate occupational radiation dose and haematopoietic malignancy mortality risks during 1983–2012. Cumulative bone marrow dose (mean 8.5 mGy, range 0–430 mGy) was estimated based on 921 134 badge monitoring measurements during 1960–1997, work histories and historical data; 35.4% of estimated doses were based on badge measurements. Poisson regression was used to estimate excess relative risk of haematopoietic cancers per 100 milligray (ERR/100 mGy) bone-marrow absorbed dose, adjusting for attained age, sex and birth year. Results: Deaths from baseline questionnaire completion through 2012 included 133 myeloid neoplasms, 381 lymphoid neoplasms and 155 leukaemias excluding chronic lymphocytic leukaemia (CLL). Based on a linear dose-response, no significant ERR/100 mGy occurred for acute myeloid leukaemia (ERR=0.0002, 95% CI <−0.02 to 0.24, p-trend>0.5, 85 cases) or leukaemia excluding CLL (ERR=0.05, 95% CI <−0.09 to 0.24, p-trend=0.21, 155 cases). No significant dose-response trends were observed overall for CLL (ERR<−0.023, 95% CI <−0.025 to 0.18, p-trend=0.45, 32 cases), non-Hodgkin lymphoma (ERR=0.03, 95% CI <−0.2 to 0.18, p-trend=0.4, 201 cases) or multiple myeloma (ERR=0.003, 95% CI −0.02 to 0.16, p-trend>0.5, 112 cases). Findings did not differ significantly by demographic factors, smoking or specific radiological procedures performed. Conclusion: After follow-up averaging 22 years, there was little evidence of a relationship between occupational radiation exposure and myeloid or lymphoid haematopoietic neoplasms.